Almanak Menara Kudus: Study of á¸¤isÄb Results in 1990 until 2019 - Fauzi, Ahmad (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2019)
Almanak Menara Kudus is the work of KH. Turaichan which is done by the method of á¸¥isÄb qaá¹â€˜Ä«. The results of the almanac, especially the initial determination of Shawwal, are sometimes different from the Government and other Islamic calendars. However, after the death of KH. Turaichan, Almanak Menara Kudus held by Sirril Wafa â€“son of KH. Turaichanâ€“ has never been different from the results of the Government calculations and other Islamic calendars. This study discusses changes in the calculation methods of the two figures from 1999 to 2019. This study is qualitative in the literature method and comparative analysis. This study concluded that in Almanak Menara Kudus, between KH. Turaichan and Sirril Wafa, there was no changes in the method. It's just that there are developments in the Sirril Wafa era, those are corrections to the horizontal parallax, refraction, and semi-diameter, so that the results are more accurate with a difference of about 1Â°.